(untitled) (Ameghiniana, 2025)
Previous efforts have recently clarified the systematics of the megalonychid sloth Eucholoeops ingens from the Early–Middle Miocene Santa Cruz Formation ( 18 to 15.6 Ma, Santacrucian Age) of Argentine Patagonia. This report continues the revision of Eucholoeops through the analysis of specimens previously assigned in the literature and museum records to this genus, but excluded from these earlier works. The comparative analyses conducted here, incorporating specimens of the closely similar Hapalops, suggest that two species of Eucholoeops, Eucholoeops ingens and Eucholoeops latifrons, also from the Santacrucian of Argentine Patagonia, are valid. Cranial and postcranial characters exhibit consistent though subtle differences between them as well as similarities, suggesting that they are specifically distinct though congeneric. Similarities include: a relatively short, wide rostrum; preorbital width nearly equivalent to or greater than the postorbital constriction; little or no maxillary extension beyond the upper caniniform alveolus; large, triangular caniniforms; mesiodistally compressed molariforms; less prominent humeral deltopectoral shelf than in Hapalops and V-shaped femoral third trochanter. E. latifrons differs from E. ingens in its smaller caniniforms; nearly equivalent preorbital and postorbital widths; maxillary extension beyond the caniniform alveolus; larger lateral margin of the humeral deltopectoral shelf; less proximally extended femoral greater trochanter; larger lesser trochanter; and less prominent trochanteric fossa and intertrochanteric crest. Exploration that these differences might be due to sexual dimorphism rather than to specific distinction suggests that it is more prudent to maintain specific status.